Radical right populism and the role of positional deprivation and inequality - Brian Burgoon; Sam van Noort; Matthijs Rooduijn; Geoffrey R. D. Underhill (Luxembourg Income Study (LIS), 2018)
This paper explores how support for radical right populist parties may be shaped by new measures of deprivation and inequality based on growth-incidence-curves, gauging growth in real household income across a country's income deciles and calculating a given decile's gains relative to the gains of other deciles. The paper argues that such positional measures capture drivers of economic resentment relevant to radical-right populism. First, radical right populism is more likely among individuals facing more "positional deprivation", those in deciles with gains that are smaller than the gains of the average, richest or poorest deciles in their own country. Second, subjective low income more strongly spurs support for radical right populist parties in polities with higher "positional inequality", where the wealthiest deciles experience greater gains than (or suffer less than) the median or poorest earners. The paper tests these expectations using individual-level survey data from sixteen European countries. It finds support for the arguments, not only in patterns of support and voting for parties in the radical right party family but also in patterns of support and voting for parties expressing more anti-globalization nationalism and authoritarianism in their party manifestos.
Keywords: 330; politics; electoral; voter; income distribution; radical-right populism; positional deprivation